2011
DOI: 10.1016/j.ijimpeng.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the behaviour and failure modes of axially compressed steel columns subjected to transverse impact

Abstract: In this study a numerical simulation of the behaviour and failure modes of axially compressed steel column subjected to transverse impact by a rigid mass at different impact speeds and locations is presented. Firstly, the capability of the present numerical model to trace the response and to predict different failure modes of transversely impacted beams and columns with and without axial compressive force has been validated. These failure modes include plastic global failure, tensile tearing failure and transv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…It is observed that the current FE simulation can predict the failure modes of 0%, 50%, and 70% axially loaded steel tube under transverse impact loading reasonably. The CHS tube with 70% axial loading has shown global failure behaviour with large lateral and axial displacement as depicted in the earlier experimental tests and numerical simulations [20,30,31]. Fig.…”
Section: Validation Of Impact Simulation Processmentioning
confidence: 56%
See 1 more Smart Citation
“…It is observed that the current FE simulation can predict the failure modes of 0%, 50%, and 70% axially loaded steel tube under transverse impact loading reasonably. The CHS tube with 70% axial loading has shown global failure behaviour with large lateral and axial displacement as depicted in the earlier experimental tests and numerical simulations [20,30,31]. Fig.…”
Section: Validation Of Impact Simulation Processmentioning
confidence: 56%
“…The surface-to-surface approach has been chosen due to more realistic stress distribution compared to node-to-surface contact algorithm [28]. Penalty and hard contact methods are adopted to define the tangential and normal behaviour of contact interaction with the value of 0.47 coefficient of friction [30]. The predefined field option in ABAQUS/Explicit is used to apply the initial velocity of 7 m/s to the indentor to cause transverse impact on the steel tube.…”
Section: Validation Of Impact Simulation Processmentioning
confidence: 99%
“…Past research and statistic data have revealed that accidental collision is one of the main causes of structural failure [2,3]. During the collision, the structural components are exposed to the operating axial compressive load as well as the lateral impact loads [4]. The collision energy is absorbed by the tubular members subjected to bending conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Steel beams develop different impact resistances while impact loads are applied at various locations. Al-Thairy and Wang [21] examined the behavior and failure modes of axially compressed steel columns subject to transverse impact by a rigid mass at varying impact speeds and locations. Ning and Zhao [22,23] completed the experimental study on the stability of aluminum alloy cantilever high beams under cylinder head impact.…”
Section: Introductionmentioning
confidence: 99%